Anti‐clogging mechanisms of a motion‐activated chest tube patency maintenance system: Histology and high‐speed camera assessment. Issue 11 (5th July 2020) - Okano, Shinji; Lobosky, Mark; Dessoffy, Raymond; Horvath, David J.; Fukamachi, Kiyotaka; Karimov, Jamshid H.
Abstract: The motion‐activated system (MAS) employs vibration to prevent intraluminal chest tube clogging. We evaluated the intraluminal clot formation inside chest tubes using high‐speed camera imaging and postexplant histology analysis of thrombus. The chest tube clogging was tested (MAS vs. control) in acute hemothorax porcine models ( n = 5). The whole tubes with blood clots were fixed with formalin–acetic acid solution and cut into cross‐sections, proceeded for H&E‐stained paraffin‐embedded tissue sections (MAS sections, n = 11; control sections, n = 11), and analyzed. As a separate effort, a high‐speed camera (FASTCAM Mini AX200, 100‐mm Zeiss lens) was used to visualize the whole blood clogging pattern inside the chest tube cross‐sectional view. Histology revealed a thin string‐like fibrin deposition, which showed spiral eddy or aggregate within the blood clots in most sections of Group MAS, but not in those of the control group. Histology findings were compatible with high‐speed camera views. The high‐speed camera images showed a device‐specific intraluminal blood "swirling" pattern. Our findings suggest that a continuous spiral flow in blood within the chest tube (MAS vs. static control) contributes to the formation of a spiral string‐like fibrin network during consumption of coagulation factors. As a result, the spiral flow may prevent formation of thick band‐like fibrin deposits sticking to the inner tube surface and causing tube clogging, and thus may positively affect chest tube patency and drainage.